Perkembangan Ragam Bahasa Dalam Komunikasi Mahasiswa di Universitas Buana Perjuangan Karawang - Sa’diah, Halia Tus; Repelita, Tridays; Putri, Nuruliza Aulia; Ramadhani, Nisa Aulia (Peneliti.net, 2025)
Language is the exchange of sound symbols produced by human speech organs, between members of a society. Communication and language have a very close relationship. Linguistic formulations and communication reviews both agree that language is defined in a way that reflects the relationship between the two. Indonesian has replaced other regional languages ​​used in Indonesia, especially in urban areas and surrounding areas, such as Sasak in Lombok, Samawa in Sumbawa, Balinese in Bali and several other areas in Lombok. These regional languages ​​are used in daily interactions. The aim of this research is to find out how different languages ​​develop in student communication in the UBP Karawang setting. The method used to collect this data is qualitative. This type is clearly asked. Students tend to use different dialect varieties, which are influenced by components such as social, territorial, social and instructive foundations. There are various student dialects in the scholastic environment consisting of formal dialects, everyday dialects, code exchange and code mixing, distance dialects, and non-verbal dialects